Ten-Day versus 14-Day Levofloxacin-Containing Triple Therapy for Second-Line Anti-Helicobacter pylori Eradication in Taiwan - Wei-Chen Tai; Chien-Hua Chiu; Chih-Ming Liang; Kuo-Chin Chang; Chung-Mou Kuo; Yi-Chun Chiu; Keng-Liang Wu; Ming-Luen Hu; Yeh-Pin Chou; Shue-Shian Chiou; King-Wah Chiu; Chung-Huang Kuo; et al. (Gastroenterology Research and Practice)
Second-line Helicobacter pylori (H. pylori) eradication with fluoroquinolone-containing triple therapy is one of the recommended treatment options, but neither 7-day nor 10-day regimens provide >90% success rates. The current retrospective study aimed to clarify the effects of 10-day and 14-day levofloxacin-containing triple therapies for second-line H. pylori eradication in a Taiwanese cohort and to evaluate the potential clinical factors influencing eradication. A total of 200 patients who failed H. pylori eradication using the standard triple therapy were prescribed with either a 10-day (EAL-10) or a 14-day (EAL-14) levofloxacin-containing triple therapy group (levofloxacin 500 mg once daily, amoxicillin 1 g twice daily, and esomeprazole 40 mg twice daily). Follow-up studies to assess treatment response were carried out 8 weeks later. Eradication rates attained by EAL-10 and EAL-14 were 75.6%; 95% –85.3% and 92.5%; 95% –98.1%, in the per protocol analysis and 68%; 95% –78.5% and 86%; 95% –93.4%, in the intention-to-treat analysis. The duration of H. pylori therapy is the independent risk factor of H. pylori eradication (). In conclusion, 14-day levofloxacin-containing triple therapy can provide a >90% H. pylori eradication rate, but 10-day treatment duration may be suboptimal. The longer duration of H. pylori therapy (14 days) is the independent risk factor.